2015
DOI: 10.11646/zootaxa.3926.2.9
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the water mite genus Hygrobates Koch, 1837 (Acari: Hydrachnidia: Hygrobatidae) from the ancient Lake Ohrid

Abstract: A new water mite species, Hygrobates zawali n. sp., is described from material collected in the ancient Lake Ohrid on the Balkan Peninsula. This species has been confused for a long time with the rhithrobiontic H. diversiporus Sokolow, 1927, known from the Caucasus (Russia) and Turkey. The new species closely resembles H. quanaticola Schwoerbel & Sepasgozarian, 1976, a little documented species described from Iran, which is here illustrated based on re-examination of the type material. Furthermore, a key for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…So far, at least 185 taxa have been described Pešić, 2015;Stocchino et al, 2013;Wysocka et al, 2013). In addition, there is a rich protist flora.…”
mentioning
confidence: 99%
“…So far, at least 185 taxa have been described Pešić, 2015;Stocchino et al, 2013;Wysocka et al, 2013). In addition, there is a rich protist flora.…”
mentioning
confidence: 99%
“…Previous studies showed that the lake is characterised by a high rate of endemism (36%, Albrecht & Wilke, 2008) compared to other ancient lakes, such as the much bigger Lake Victoria (31.3%). So far, nearly 350 endemic species have been described from Lake Ohrid, of which at least 188 are animals (Albrecht & Wilke, 2008; Hauffe et al., 2015; Pešič, 2015; Stelbrink et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that, taking into account its surface, the lake is characterised by a high rate of endemism (36%) compared to other ancient lakes (Albrecht & Wilke, 2008), such as for example the much bigger Lake Victoria (31.3 %). So far, nearly 350 endemic species have been described from Lake Ohrid, of which at least 188 are animals (Albrecht & Wilke, 2008;Hauffe et al, 2015;Pešič, 2015;Stelbrink et al, 2016;Stocchino et al, 2013). Lake Ohrid region was designated a UNESCO World Heritage Site for its natural values in 1979 and for its cultural heritage values a year later (Centre, 2022).…”
Section: Introductionmentioning
confidence: 99%